Faktor Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntansi (PPAK) di Indonesia - Yanti, Ullifah (Jurnal Pendidikan Akuntansi (JPAK), 2024)
Professional Accounting Education (PPAK) plays an important role in equipping students majoring in accounting to become experts in the field of accounting. The aim of this research is to determine how certain factors influence accounting students' desire to take part in a professional accounting program, as well as evaluate the impact of the academic environment on accounting students' intentions to complete PPAK. This research method uses a "charting the field" approach. The results of the research are as follows. (1) Motivational factors such as qualifications, career opportunities, and financial aspects have a significant influence on students' interest in participating in vocational training programs. (2) motivation, career opportunities and financial conditions have a significant effect on students' interest in participating in PPAK education. (3) Motivational factors such as qualifications, academic achievement and emotional intelligence make a positive contribution to students' interest in pursuing professional accounting education. (4) Motivational factors such as professional and social motivation do not have a significant influence on students' interest in pursuing PPAK education. (5) Motivational factors such as program quality, career opportunities, financial efficiency, social motivation, perception of training costs, and perception of study duration have a significant influence on student interest in professional accounting education. .